KEWIRAUSAHAAN DALAM PERSPEKTIF ISLAM - Elfa Yuliana (Ta'dib: Jurnal Pendidikan Islam dan Isu-Isu Sosial, 2017)
Entrepreneurship is a creative effort which creates values from nothing comes into being. It is possible to be enjoyed by many people. The increasing number of entrepreneur will impact the strengthten of economic state. It has been proved through the nation historical journey that Small and Medium Enterprises (UKM) such as an economic basis which has strongest durability to face against multidimensional crisis. According to the statements, Islam strongly suggests people to endeavor every effort and work since works became the very basic modal to gain success. Thus, hard work behavior must be owned by an entrepreneur. In this case, discipline substance has the important role play. There is one more important element in gaining success of hard work, which is to give over the rest to Allah SWT. The hard work accompanied by prayer will gain success Insha Allah. In entrepreneurship field there are some points that must be maintained by the entrepreneur to achieve his aim as worth as worship. First, intention straightening, and aqidah consolidating in the beginning of the commerce. People should put an intention to their commerce business to be spared from greed and make the religion as the base of the commerce conduct. Second, putting the intention to trade in their effort to fulfil Fardhu Kifayah and maintaining Allah SWT in their memory. Third, willing to accept and not being greedy to the market and commerce. Fourth, avoiding shubhat (disguised between halal and haram) and pay close attention to the all physical trade practices. Entrepreneurship in Islam perspective is a noble effort as what stated in the Hadith “Narrated Ahmad: You should do the trade (entrepreneurship). Because inside the trade there are 90 percent of rizq door”